How perceived organizational politics cause work-to-family conflict? Scoping and systematic review of literature - Sumbol Fiaz; Muhammad Azeem Qureshi (Future Business Journal, 2021)
Work-family conflict is a subject of interest for researchers in the field of organizational behavior for decades because of its negative impact on an individual's life. The existing literature identified that workplace stressors contribute to work-family conflict and Perceived Organizational Politics emerged as an aversive workplace stressor. From empirical pieces of evidence, it is observed that perceived organizational politics and work-family conflict are indirectly associated with each other, and their impact on employees is unavoidable. To explore this uncovered relationship, at first, this study used a keywords co-occurrence network mapping approach and found that perceived organizational politics and work-family conflict are associated with each through various workplace variables. Further, with the help of a scoping review identify those specific variables, and, lastly, a systematic review approach used to identify a mechanism of how these identified variables form an association between perceived organizational politics and work-family conflict. Based on the findings of the systematic review, this study proposed a conceptual framework that extends the existing literature by providing new insight into concepts of perceived organizational politics by linking it with work-family conflict. This study introduced a novel way to develop a conceptual framework by linking three distinct approaches of research. In the last, this study proposed recommendations for future research.
Keywords: 650; Emotional intelligence; Negative affectivity; Organizational behavior; Perceived organizational politics; Perceived organizational support; Psychological wellbeing; Social support; Work-to-family conflict